Factors Influencing Organizational Commitment in Technical-Based Public Learning Institutions - Che Norazizi, Che Mastar (2012)
The objective of this study is to investigate the relationship between Affective Commitment, Normative Commitment, Perceived Fairness, Training and Job Characteristics with Organizational Commitment. A total 125 respondents participated in this study. All five factors were found to have a positive relationship with Organizational Commitment. The Pearson correlation analysis conducted showed that Perceived Fairness is the strongest factor influencing Organizational Commitment. The other four factors showed a weak relationship with Organizational Commitment. The labeling of an organization as 'fair" can be made off the basis of perception and reality. Fairness is ideally seen and felt throughout all levels of the organization (there by confirming it is real rather than just perceived) and can take many form in the workplace; application of policies, procedures and the presence of unions also help in the organization activities. Equity, and in essence-fairness, is a key driver of employee engagement